74.1k views
4 votes
Please explain how to solve the problem.

Please explain how to solve the problem.-example-1
User Dmcer
by
5.0k points

1 Answer

1 vote

Answer:

Part 1)
f(125)=6

Part 2)
f(-64)=-3

Explanation:

we have


f(x)=\sqrt[3]{x} +1

Part 1) Find f(125)

we know that

f(125) is the value of the function f(x) when the value of x is equal to 125

so

For x=125

substitute in the function


f(125)=\sqrt[3]{125} +1

Remember that


125=5^(3)

substitute


f(125)=\sqrt[3]{5^(3)} +1

Applying the power of rule


\sqrt[3]{5^(3)}=(5^(3))^{(1)/(3)}= (5)^{3*(1)/(3)}=5

substitute


f(125)=5 +1=6

Part 2) Find f(-64)

we know that

f(-64) is the value of the function f(x) when the value of x is equal to -64

so

For x=-64

substitute in the function


f(-64)=\sqrt[3]{-64} +1

Remember that


-64=-4^(3)

substitute


f(-64)=\sqrt[3]{-4^(3)} +1

Applying the power of rule


\sqrt[3]{-4^(3)}=(-4^(3))^{(1)/(3)}= (-4)^{3*(1)/(3)}=-4

substitute


f(-64)=-4 +1=-3

User Steven Graham
by
5.9k points